123456789101112131415161718192021222324252627282930313233343536373839404142434445464748 |
- from sympy.ntheory.multinomial import (binomial_coefficients, binomial_coefficients_list, multinomial_coefficients)
- from sympy.ntheory.multinomial import multinomial_coefficients_iterator
- def test_binomial_coefficients_list():
- assert binomial_coefficients_list(0) == [1]
- assert binomial_coefficients_list(1) == [1, 1]
- assert binomial_coefficients_list(2) == [1, 2, 1]
- assert binomial_coefficients_list(3) == [1, 3, 3, 1]
- assert binomial_coefficients_list(4) == [1, 4, 6, 4, 1]
- assert binomial_coefficients_list(5) == [1, 5, 10, 10, 5, 1]
- assert binomial_coefficients_list(6) == [1, 6, 15, 20, 15, 6, 1]
- def test_binomial_coefficients():
- for n in range(15):
- c = binomial_coefficients(n)
- l = [c[k] for k in sorted(c)]
- assert l == binomial_coefficients_list(n)
- def test_multinomial_coefficients():
- assert multinomial_coefficients(1, 1) == {(1,): 1}
- assert multinomial_coefficients(1, 2) == {(2,): 1}
- assert multinomial_coefficients(1, 3) == {(3,): 1}
- assert multinomial_coefficients(2, 0) == {(0, 0): 1}
- assert multinomial_coefficients(2, 1) == {(0, 1): 1, (1, 0): 1}
- assert multinomial_coefficients(2, 2) == {(2, 0): 1, (0, 2): 1, (1, 1): 2}
- assert multinomial_coefficients(2, 3) == {(3, 0): 1, (1, 2): 3, (0, 3): 1,
- (2, 1): 3}
- assert multinomial_coefficients(3, 1) == {(1, 0, 0): 1, (0, 1, 0): 1,
- (0, 0, 1): 1}
- assert multinomial_coefficients(3, 2) == {(0, 1, 1): 2, (0, 0, 2): 1,
- (1, 1, 0): 2, (0, 2, 0): 1, (1, 0, 1): 2, (2, 0, 0): 1}
- mc = multinomial_coefficients(3, 3)
- assert mc == {(2, 1, 0): 3, (0, 3, 0): 1,
- (1, 0, 2): 3, (0, 2, 1): 3, (0, 1, 2): 3, (3, 0, 0): 1,
- (2, 0, 1): 3, (1, 2, 0): 3, (1, 1, 1): 6, (0, 0, 3): 1}
- assert dict(multinomial_coefficients_iterator(2, 0)) == {(0, 0): 1}
- assert dict(
- multinomial_coefficients_iterator(2, 1)) == {(0, 1): 1, (1, 0): 1}
- assert dict(multinomial_coefficients_iterator(2, 2)) == \
- {(2, 0): 1, (0, 2): 1, (1, 1): 2}
- assert dict(multinomial_coefficients_iterator(3, 3)) == mc
- it = multinomial_coefficients_iterator(7, 2)
- assert [next(it) for i in range(4)] == \
- [((2, 0, 0, 0, 0, 0, 0), 1), ((1, 1, 0, 0, 0, 0, 0), 2),
- ((0, 2, 0, 0, 0, 0, 0), 1), ((1, 0, 1, 0, 0, 0, 0), 2)]
|